The Diversity of Local Wisdom, Art and Cultural in Yangon, Republic of the Union of Myanmar - et. al., Arunee Charoensup, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: The Republic of the Union of Myanmar has the largest territory in South East Asia, border with China, India and Thailand which results the diversity in local wisdom, art and cultural and also ethnic groups. This study aims to gather the knowledge and develop multimedia of local wisdom, art and cultural in Yangon. For data collection, both primary data (survey and interview) and secondary data are applied in this research. This study is the research collaboration between Thepsatri Rajabhat University and University of Yangon. The series of multimedia in ''The Diversity of Local Wisdom, Art and Cultural in Yangon, Republic of the Union of Myanmar'' are developed in 7 categories as 1) Myanmar..the land of rice field and river, 2) The local wisdom in performing art, 3) Yangon, 4) The local wisdom in art and craft, 5) The local wisdom in art and cultural, 6) The biodiversity and tourist attraction in Yangon, 7) The local wisdom in Myanmar cuisine. The evaluation of production quality by 5 experts reveals that the multimedia is attractive with useful and understandable content/sound, also appropriate to utilize as a learning resource.